Comprehensive Testing of Chemotherapy and Immune Checkpoint Blockade in Preclinical Cancer Models Identifies Additive Combinations - Principe, Nicola; Aston, Wayne J.; Hope, Danika E.; Tilsed, Caitlin M.; Fisher, Scott A.; Boon, Louis; Dick, Ian M.; Chin, Wee Loong; McDonnell, Alison M.; Nowak, Anna K.; Lake, Richard A.; Chee, Jonathan; et al. (Frontiers in Immunology, 2022)
Antibodies that target immune checkpoints such as cytotoxic T lymphocyte antigen 4 (CTLA 4) and the programmed cell death protein 1/ligand 1 (PD-1/PD-L1) are now a treatment option for multiple cancer types. However, as a monotherapy, objective responses only occur in a minority of patients. Chemotherapy is widely used in combination with immune checkpoint blockade (ICB). Although a variety of isolated immunostimulatory effects have been reported for several classes of chemotherapeutics, it is unclear which chemotherapeutics provide the most benefit when combined with ICB. We investigated 10 chemotherapies from the main canonical classes dosed at the clinically relevant maximum tolerated dose in combination with anti-CTLA-4/anti-PD-L1 ICB. We screened these chemo-immunotherapy combinations in two murine mesothelioma models from two different genetic backgrounds, and identified chemotherapies that produced additive, neutral or antagonistic effects when combined with ICB. Using flow cytometry and bulk RNAseq, we characterized the tumor immune milieu in additive chemo-immunotherapy combinations. 5-fluorouracil (5-FU) or cisplatin were additive when combined with ICB while vinorelbine and etoposide provided no additional benefit when combined with ICB. The combination of 5-FU with ICB augmented an inflammatory tumor microenvironment with markedly increased CD8+ T cell activation and upregulation of IFN𝛾, TNF𝛼 and IL-1β signaling. The effective anti tumor immune response of 5-FU chemo-immunotherapy was dependent on CD8+ T cells but was unaffected when TNF𝛼 or IL-1β cytokine signaling pathways were blocked. Our study identified additive and non-additive chemotherapy/ICB combinations and suggests a possible role for increased inflammation in the tumor microenvironment as a basis for effective combination therapy.